Analysis of Satisfaction and Loyalty Among Users of the Jakarta Mass Rapid Transit: What is the Role of Service Quality, Facilities, and Perceived Price - Rahmanita, Patricia Putri; Suhud, Usep; Krissanya, Nofriska (LPPPIPublishing, 2025)
This study aims to examine the effects of service quality, facilities, and perceived price on customer satisfaction and customer loyalty among users of the MRT Jakarta public transportation system. A quantitative approach was employed through an online survey using a 6-point Likert scale. Respondents were MRT Jakarta users aged 17–64, residing in DKI Jakarta, who had used the service at least three times within the past week. Data were analyzed using SPSS for preliminary analysis and Structural Equation Modeling (SEM) via AMOS for model testing. The results indicate that service quality, facilities, and perceived price each have a positive and significant effect on both customer satisfaction and customer loyalty. Additionally, customer satisfaction significantly influences customer loyalty. These results suggest that improvements in service quality, the provision of convenient and well-maintained facilities, and the perception valuable pricing contribute significantly to enhancing satisfaction and long-term loyalty among MRT Jakarta users.